« A thrust at truth and a lie » : The Crying of Lot 49 ou le langage en quête de vérité - Jean-Yves Pellegrin (Sillages Critiques)
The relation of The Crying ofLot 49 to the detective novel may not be a simple matter of borrowing some of the characteristic patterns and features of the genre. Indeed, like detective narratives, Pynchon’s novel seems to intimate that some heuristic power is at work in its text. Yet, while the detective novel tends to identify this power with the narrative performance itself, Lot 49 insists on the utter inability of narratives to work out a puzzle and find out the truth. This denial prompts the reader to turn away from the narrative and look for the heuristic power of the text in language itself. A thrust at truth, the language in Pynchon’s book is indeed pregnant with meaning and always on the verge to blaze out into an epiphanic flash.